Exploring travel patterns of Chinese holiday tourists in Western Australia - Zea Carcausto, Mikhail Prude; Siwale, Maka; Xia, Cecilia; Reiners, Torsten; Holmes, Kirsten (The University of Newcastle, 2018)
The Chinese outbound market is considered extremely important for Australia. This is the fastest growing international market for Western Australia and both industry and government have taken steps to target this high yield cohort of tourists. Chinese tourists to WA typically visit Perth, with much fewer visiting regional WA and our understanding of Chinese tourists' travel patterns in WA is limited. Using the International Visitor Survey data, this paper explores the characteristics of Chinese holiday tourists to WA and their favourite destinations within the state. Using routing analysis, itineraries in regional WA are calculated in order to understand how better to promote dispersion of Chinese tourists outside the state capital city. Routing software offers opportunities to tourism marketing associations and tourism businesses to develop and promote itineraries for specific target cohorts. These preferred destinations are then reviewed to identify whether their service provision aligns with the preferences of Chinese tourists leading to recommendations for tourism development in regional WA.